The Impact of Non‐Equilibrium Plasma Distributions on Solar Wind Measurements by Vigil's Plasma Analyser - H. Zhang; D. Verscharen; G. Nicolaou (Space Weather, 2024)
Abstract In order to protect society from space weather impacts, we must monitor space weather and obtain early warnings for extreme events if possible. For this purpose, the European Space Agency is currently preparing to launch the Vigil mission toward the end of this decade as a space‐weather monitor at the fifth Lagrange point of the Sun–Earth system. Vigil will carry, amongst other instruments, the Plasma Analyser (PLA) to provide quasi‐continuous measurements of solar wind ions. We model the performance of the PLA instrument, considering typical solar wind plasma conditions, to compare the expected observations of PLA with the assumed input conditions of the solar wind. We evaluate the instrument performance under realistic, non‐equilibrium plasma conditions, accounting for temperature anisotropies, proton beams, and the contributions from α‐particles. We examine the accuracy of the instrument's performance over a range of input solar wind moments. We identify sources of potential errors due to non‐equilibrium plasma conditions and link these to instrument characteristics such as its angular and energy resolution and its field of view. We demonstrate the limitations of the instrument and potential improvements such as applying ground‐based fitting techniques to obtain more accurate measurements of the solar wind even under non‐equilibrium plasma conditions. The use of ground processing of plasma moments instead of on‐board processing is crucial for the extraction of reliable measurements.